2008
DOI: 10.1021/jm701321p
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Simplified Tubulysin Analogues

Abstract: An efficient route for the synthesis of the tubulysin family of antimitotic peptides was developed. Simplified tubulysin analogues were synthesized to define the minimum pharmacophore required for cytotoxicity. Simplified tubulysin analogues retain significant cytotoxicity and reveal important preliminary structure-activity relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The tubulysins are a compelling drug class for ADCs as they are highly potent across a wide range of cancer cell lines and retain potency on MDR þ cell lines like L428 and 786-O (Table 1). We and others (15) have demonstrated that a secondary amine at the N-terminus of two distinct tubulysin analogues significantly impairs cytotoxic activity relative to the N-methylated tertiary amine parent compounds. Conversion of the C-terminal carboxylate to include a circulation-stable conjugatable group appears more promising.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The tubulysins are a compelling drug class for ADCs as they are highly potent across a wide range of cancer cell lines and retain potency on MDR þ cell lines like L428 and 786-O (Table 1). We and others (15) have demonstrated that a secondary amine at the N-terminus of two distinct tubulysin analogues significantly impairs cytotoxic activity relative to the N-methylated tertiary amine parent compounds. Conversion of the C-terminal carboxylate to include a circulation-stable conjugatable group appears more promising.…”
Section: Discussionmentioning
confidence: 78%
“…However, modification of tubulysins to introduce a functional group for conjugation is commonly not well tolerated. For example, the N-terminal Ndesmethyl analogue of a keto-tubulysin derivative was found to be 100-fold less potent than the tertiary amine-containing parent (15). Similarly, conversion of N…”
Section: Introductionmentioning
confidence: 99%
“…Competition studies suggest a binding site close to the peptide site of the vinca domain of β tubulin (Khalil et al ., 2006). Due to the limited natural supply of tubulysin and its complicated synthesis, clinical development has, to date, been hampered (Raghavan et al ., 2008). By studying the pathway of tubulysin biosynthesis in myxobacteria, Prt was first postulated and then identified as a biosynthetic intermediate (Ullrich et al ., 2009a) that is synthetically accessible, and can be easily derivatized (Ullrich et al ., 2009b; Burkhart et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A novel group of microtubule‐depolymerizing natural products of myxobacterial origin, the tubulysins, has recently been described (Sasse et al ., 2000), and has turned out to be highly potent against some tumour cell lines (Sasse et al ., 2000; Kaur et al ., 2006). Due to the supply issue mentioned earlier, several attempts have been made to synthesize simplified tubulysin derivatives (Raghavan et al ., 2008; Ullrich et al ., 2009a). The most promising approach to date is the synthesis of pretubulysin (Prt), a putative precursor of some tubulysins, which has only a slight loss of potency as compared to tubulysin itself (Ullrich et al ., 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…9-11 However, the structural complexity of natural products, such as intricate ring systems and numerous chiral centers, may lead to limited supplies and hamper mechanism of action studies and clinical development 12. For this reason, structural simplification of natural products is a powerful and highly productive tool for lead development and analog design 13. A well-known example is the simplification of morphine, which led to the clinically used medicines levophanol and meperidine 14.…”
Section: Introductionmentioning
confidence: 99%